Study on mobile target real-time image registration based on improved SURF algorithm - Gang JU; Liang YUAN; Xiao-yue LIU; Hao-en YUE (Tongxin xuebao)
For the unstability of the real-time visual image characteristic point extraction and matching for the mobile target,an improved registration method of the multiple algorithm-fusion was introduced.Firstly,the method of bilateral filtering,Canny edge detection and morphological processing,was adopted to get the more robust image's edge map.And the founded points were limited in this edge map,then the Hessian matrix of SURF based on the discrete Gaussian-Hermite moment was modified.The character description vector was redefined in the algorithm.Following the above analysis,the Kendall coefficient constraint was discussed in image matching characteristic points.Secondly,the spectral radiant color invariant model and the I_SURF algorithm were used to match the real-time color image.Finally,the improved algorithm was combined with the update algorithm of adaptive target to match the mobile target in indoor environment.The experimental results show that the static image registration accuracy of the improved algorithm is higher than that of the SURF algorithm,and also the stability of the mobile image feature points extraction and the registration number have achieved over 97% under different rotating scales.